Prevalência e fatores associados às dificuldades alimentares em escolares entre seis meses a seis anos de idade - Pinto, Malu Micilly Porfírio Santos (2024)
Introduction: Childhood feeding difficulties is a term used to refer to feeding problems in children, characterized as an feeding disorder in which both physiological and psychosocial factors contribute to its onset and maintenance. Objective: To identify the prevalence of feeding difficulties in schoolchildren aged 6 months to 6 years, as well as to investigate whether there is an association between the prevalence of such difficulties and clinical and sociodemographic aspects. Method: Primary observational study, with a cross-sectional design, prevalence type. The target audience were schoolchildren aged between 6 months and 6 years old, regularly enrolled in the year 2023, in educational institutions in the municipality of Itaporanga, Paraíba, Brazil. To select participants, stratified random sampling was carried out, with allocation proportional to the size of the strata, resulting in a final sample of 349 children. The identification of feeding difficulties and children's clinical and sociodemographic characteristics were obtained using two instruments: Brazilian Infant Feeding Scale - classified as follows: without feeding difficulties (scores ≤ 60) and with feeding difficulties (scores > 60) - and personal information collection instrument, both with parents/guardians as respondents. To evaluate the contribution of secondary variables to the binary outcome of the main variable, the following decision models were implemented: multiple logistic regression and binary classification model (weight of evidence technique together with information value). Results: Of the total study sample (n = 349), 30% of children demonstrated some level of feeding difficulty. The predominant age group corresponded to the range between 25 and 83 months (98.6%). The percentages regarding gender were very close, but with greater representation for males (51.3%). Of the children investigated, 28.4% were only children and 47.0% were the couple's first-born child. With regard to the child's parents, both fathers (73.9%) and mothers (89.7%) were aged 40 or less. The most frequent categories related to parents' education were: no education and primary level, both for fathers (31.5% + 23.5% = 55%) and mothers (20.4% + 20.9% = 47.3%). Regarding monthly family income, the majority of families (65.3%) received less than the minimum wage. As for the educational institution, the children investigated were mostly enrolled in public schools (52.1%), with 76.5% belonging to early childhood education. Regarding the implementation of decision models, the data revealed in their analysis the identification of the same factors associated with children's feeding difficulties, namely: pre-chewing practice (performed by parents/caregivers), disregard for signs of satiety in the child and low education level of the mother.Conclusion: Recognizing and better understanding the factors associated with children's feeding difficulties can help in 10 early diagnosis and prevention of new cases, as well as in appropriate therapy and mitigation of damage to the child's growth and neurodevelopment process. Furthermore, the data from this study can collaborate in the management decision-making process and serve as a tool for possible expansions and/or development of public policies aimed at child food and nutrition.